2022
DOI: 10.20471/acc.2022.61.s1.03
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hypertension following COVID-19: A retrospective study of patients in a Central European tertiary care center

Abstract: The aim of this study was to determine the frequency of newly verified or worsened existing hypertension in patients who had coronavirus 2019 .to be categorized as a COViD-19 patient, a positive reverse-transcription polymerase chain reaction test at a single point in time was required. The patients' age, history, laboratory values and antihypertensive therapy of patients were recorded.in one year, 32 of 199 patients studied had either newly verified (15) or worsened existing (17) arterial hypertension. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
0
18
1
2
Order By: Relevance
“…In two confirmed COVID-19 patients enrolled cohort studies, BP was significantly higher in the post-COVID-19 period than upon admission [285] , [286] , and Ang II signaling upregulation driven by SARS-CoV-2 infection might play a critical role in the progression of new-onset hypertension [285] . Another retrospective study also demonstrated that arterial hypertension following SARS-CoV-2 infection, either newly verified or worsened existing, was a relatively common occurrence [310] . However, some cross-sectional research showed that COVID-19 did not influence blood pressure, particularly in young subjects [311] , [312] , [313] , [314] .…”
Section: The Role Of Counter-regulatory Ras To Link Hypertension and ...mentioning
confidence: 98%
“…In two confirmed COVID-19 patients enrolled cohort studies, BP was significantly higher in the post-COVID-19 period than upon admission [285] , [286] , and Ang II signaling upregulation driven by SARS-CoV-2 infection might play a critical role in the progression of new-onset hypertension [285] . Another retrospective study also demonstrated that arterial hypertension following SARS-CoV-2 infection, either newly verified or worsened existing, was a relatively common occurrence [310] . However, some cross-sectional research showed that COVID-19 did not influence blood pressure, particularly in young subjects [311] , [312] , [313] , [314] .…”
Section: The Role Of Counter-regulatory Ras To Link Hypertension and ...mentioning
confidence: 98%
“…Сходные данные были получены в Хорватии в результате обследования 200 пациентов, перенесших новую коронавирусную инфекцию [24]. Выявлено, что примерно 1 из каждых 7 человек, инфицированных COVID-19, подвержен риску развития либо новых случаев АГ или обострения и ухудшения уже существующего заболевания [24].…”
Section: общность патогенеза артериальной гипертензии и Covid-19unclassified
“…Предполагается, что около 10% населения в целом будут страдать от постковидной АГ [41]. С целью выявления этой категории пациентов, учитывая длительное бессимптомное течение АГ, предлагается обследовать всех пациентов, перенесших COVID-19, через 6-12 месяцев после инфекции [24,41].…”
Section: аг и постковидный синдромunclassified
“…It has been established that some patients continue to show systematic symptoms even after recovery from the acute infection ( 6 ). Although it has been hypothesized and proven that COVID-19, a virus with strong tropism for angiotensin-converting enzyme 2 (ACE2) receptors, which are present in most of the organ systems of the human body, causes lasting changes on both the molecular and macroscopic level, the exact epidemiological dynamics and clinical manifestations of post-COVID have not been sufficiently researched ( 7 ).This post-COVID syndrome was first observed in mid-2020, and by now evidence supports that 10%-35% of cases may continue as post-COVID symptoms, while hospitalized patients may have an incidence rate of as much as 85% ( 8 , 9 ).Post-COVID syndrome is defined as continuing of symptoms or complications that occur 4 weeks after the onset of the original symptoms, and it is multi-systemic in nature. Furthermore, post-COVID syndrome is differentiated into subacute (lasting for 4-12 weeks after the acute illness) and chronic (lasting for more than 12 weeks) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%